Learning English in the shadow: Patterns and implications of English private tutoring in Vietnam - Nguyen, Lan Thi Huong; Vu, Thao (Universitas Syiah Kuala, 2024)
Private tutoring has grown in prominence on a global scale. While research in this area has increased in recent decades, there remains a lack of focus on English private tutoring. This gap is particularly evident in Vietnam, where research on English private tutoring has not kept pace with its growing popularity. This article sheds light on the prevalence of English private tutoring among students in public high schools in Vietnam. The study examines the rate, patterns of enrolment, the reasons for its popularity and the perceived effectiveness of English private tutoring. Based on questionnaire data collected from 583 urban, regional, and rural school students, the findings revealed an enrolment rate of over 75%, with notable disparities in enrolment patterns among students in different socio-economic areas. However, despite the prevalence of private tutoring, the research findings revealed a modest impact of such tutoring on student academic performance, evidenced by over 75% of the students reporting slight improvement in their communicative skills. Irrespective of academic achievement levels and backgrounds, private tutoring has been a widespread and normalised educational practice, reflecting the nature of social and educational competition. The study emphasises the need for more proactive measures to regulate the practice before it is well-engrained as part of the culture.